Primary Pleuropulmonary Synovial Sarcoma: Report of Two Cases and a Comprehensive Review of the Literature. (16th March 2022) - Khalili, Neda; Askari, Elham; Khalili, Nastaran; Daneshvar-Kakhki, Aboulghasem; Sadr, Makan; Haseli, Sara; Pourabdollah Toutkaboni, Mihan
Abstract: Primary sarcomas of the lung represent less than 0.5% of all primary lung tumors and comprise a heterogeneous group of malignancies including synovial sarcoma (SS). Primary pleuropulmonary SS has non-specific presentations, such as chest pain, shortness of breath and cough, and its associated imaging features resemble those of other intrathoracic malignancies. The diagnosis of these tumors needs to be confirmed by cytogenetic and molecular studies. Here, we describe two rare cases of primary pleuropulmonary SS who were admitted to our hospital. We also provide a concise review of clinical, radiological, and histopathological characteristics of pleuropulmonary SS after exploring 168 studies (415 corresponding patients) that were identified through a literature search.